Monosomy 22q11 in patients with pulmonary atresia, ventricular septal defect, and major aortopulmonary collateral arteries. Issue 2 (1st February 1998) - Hofbeck, Michael; Rauch, Anita; Buheitel, Gernot; Leipold, Georg; von der Emde, Jürgen; Pfeiffer, Rudolf; Singer, Helmut
Abstract : Objective: To describe the morphology of the pulmonary arteries in patients with pulmonary atresia, ventricular septal defect, and major aortopulmonary collateral arteries with and without monosomy 22q11. Design: A retrospective analysis of all patients with this congenital heart defect who are being followed at the University Children's Hospital Erlangen. Setting: A tertiary referral centre for paediatric cardiology and paediatric cardiac surgery. Patients: 21 patients with pulmonary atresia, ventricular septal defect, and major aortopulmonary collateral arteries. Monosomy 22q11 was diagnosed by fluorescent in situ hybridisation using the D22S75 probe (Oncor). The morphology of the pulmonary arteries was assessed on the basis of selective angiograms. Results: 10 patients (48%) were shown to have a microdeletion in 22q11 (group I). There was no difference with respect to the presence of confluent central pulmonary arteries between these patients (80%) and the remaining 11 patients (group II) without monosomy 22q11 (91%). Patients of group I, however, more often had arborisation anomalies of the pulmonary vascular bed (90% in group I v 27% in group II). Because of the more severe abnormalities of the pulmonary arteries, a biventricular repair had not been possible in any of the children with monosomy 22q11, though repair had been carried out in 64% of the children in group II. Conclusions: The developmental disturbance caused by monosomy 22q11 seems to impair the connection of the peripheral pulmonary artery segments to the central pulmonary arteries in patients with pulmonary atresia, ventricular septal defect, and major aortopulmonary collateral arteries, resulting in a lower probability of biventricular repair.